Factors that Influence Generation Z's Interest in Using the Cash Waqf Linked Sukuk Platform: UTAUT Theory (Study Case in Medan City) - Annisa, Dwi Nur; Imsar, Imsar; Harahap, Muhammad Ikhsan (Journal of Public Representative and Society Provision, 2024)
This study aims to analyze the factors that influence the behaviour intention of generation Z using the Cash Waqf Linked Sukuk (CWLS) platform by adopting the concept of the Unified Theory of Accaptance and Use of Technology (UTAUT) model. The CWLS platform acts as a financial endowment investment where the profits are directed by nadhir waqf to support the ummah. This study used the primary data that is collected by using the online survey questionnaires, and then the analysis is conducted using partial least squares (PLS) regression. The survey conducted on generation Z in in the city of Medan, sample used in this study 100 respondents. The empirical study shows that all the variables except for performance expectancy have a significant positive effect on the intention of generation Z to use Cash Waqf Linked Sukuk (CWLS) platform. The present study will help the waqf institutions and the government to develop more engaging waqf strategies for generation Z. Furthermore, this study will contribute to the existing literature especially on the factors influencing the adoption of the waqf-based platform mode.